Degradation of plasma membrane phosphatidylcholine appears not to affect the cellular cholesterol distribution - MI Pörn; MP Ares; JP Slotte (Journal of Lipid Research, 1993)
To clarify the role of possible cholesterol/phosphatidylcholine interactions in cellular cholesterol distribution, we have used a phosphatidylcholine-specific phospholipase C from Bacillus cereus to degrade the cell surface phosphatidylcholine of cultured human fibroblasts. Of cellular phosphatidylcholine, approximately 15% was susceptible to degradation by the phospholipase. In spite of the dramatic redistribution of cellular cholesterol that can be observed after sphingomyelin depletion, the degradation of cell surface phosphatidylcholine did not affect the distribution of cholesterol in fibroblasts. In cholesterol-depleted cells as well as in cholesterol-loaded cells, the size of the cell surface cholesterol pool (susceptible to cholesterol oxidase) remained unchanged after phosphatidylcholine degradation. The rate of cholesterol esterification with [3H]oleic acid and the rate of [3H]cholesterol efflux from fibroblasts to high density lipoproteins also remained unchanged after degradation of plasma membrane phosphatidylcholine. An increase in the level of [3H]cholesterol efflux to high density lipoproteins was observed after degradation of plasma membrane sphingomyelin with exogenous sphingomyelinase, in-contrast to earlier reports, where no such effect was observed. The results suggest that interactions between cholesterol and phosphatidylcholine in the fibroblast plasma membranes are less important than cholesterol/sphingomyelin interactions for the asymmetric distribution of cellular cholesterol.